Viral RNA patterns and high viral load reliably define oropharynx carcinomas with active HPV16 involvement - Holzinger, Dana; Dyckhoff, Gerhard; Bosch, Franz X. (Cancer research, 2012)
Oropharyngeal squamous cell carcinomas (OPSCC) that are associated with human papilloma virus (HPV) infection carry a more favorable prognosis than those that are HPV-negative. However, it remains unclear which biomarker(s) can reliably determine which OPSCC specimens are truly driven by HPV infection. In this study, we analyzed 199 fresh-frozen OPSCC specimens for HPV DNA, viral load, RNA expression patterns typical for cervical carcinomas (CxCaRNA+), and the HPV-targeted tumor suppressor protein p16INK4a as markers for HPV infection. In this set of specimens, there was a 49% prevalence of DNA for the cancer-associated HPV type 16 (HPV+). However, there was only a 16% prevalence of high viral load and only a 20% prevalence of CxCaRNA+, a marker of HPV16 carcinogenic activity. Among the CxCaRNA+ tumors, 78% of the specimens exhibited overexpression of p16INK4a, which also occurred in 14% of the HPV-negative tumors. Using a multivariate survival analysis with HPV negativity as the reference group, CxCaRNA+ as a single marker conferred the lowest risk of death [HR = 0.28, 95% confidence interval (CI), 0.13-0.61] from oropharyngeal cancer, closely followed by high viral load (HR = 0.32, 95% CI, 0.14-0.73). In contrast, a weaker inverse association was found for OPSCC that were HPV+ and p16INK4a high (HR = 0.55, 95% CI, 0.29-1.08). In summary, our findings argued that viral load or RNA pattern analysis is better suited than p16INK4a expression to identify HPV16-driven tumors in OPSCC patient populations.